Informe de Pasantía sobre Punto Hogar del Meta S.A.S - Garcia Polania, Karol Dayanna (Universidad Antonio Nariño, 2025)
During the internship at Punto Hogar del Meta S.A.S., objectives were defined to support the company's import and global expansion strategy. A foreign trade consulting program was conducted that addressed aspects such as regulations, customs procedures, and logistics, providing key tools to facilitate internationalization. The viability of three potential markets was investigated through a preselection matrix related to market size, entry barriers, and competition, which uncovered strategic opportunities. International suppliers were also identified and evaluated based on their production capacity, quality standards, and delivery conditions. As a result, product diversity and the strength of their imports increased, paving the way for business relationships. These initiatives have improved Punto Hogar's competitive advantage within the national and international market, facilitating future expansion.